The Application of Psychological Identity in Olympic Multicultural Education - Zhongsheng Jiang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Since its inception, the contemporary Olympic Games have increasingly eliminated regional, racial, and ideological barriers. This research is undertaken to analyze the influence of multiculturalism on psychological harmony based on the notion of the culture-psychological relationship to conduct innovative research and provide solutions for constructing psychological harmony and harmonious society. A random sample of 553 university students from a university was chosen using the "Psychological Harmony Scale" and "Cultural Impact Scale," and SPSS 13 was used to analyze the data. In addition, AMOS7.0 was utilized to develop a structural equation model, primarily for psychological harmony and multicultural variables, to conduct mean comparison t-tests and multicultural influence on psychological harmony to conduct multiple regression analyses, optimal scale analyses, and its significance test. The results revealed that male students had a substantially higher level of emotional harmony than female students (p<0.05). Cognitive harmony, behavioral harmony, self-harmony, and total psychological harmony did not substantially differ between gender groups (p>0.05). Four elements affected the psychological harmony of urban students as a whole. In today's multicultural culture, the function of education has also evolved. According to the findings of this study, cultural factors influence psychological harmony in several ways. In addition, this study found that personality mediates the effect of culture on psychological harmony.